Progressivity, government size, and redistribution in an optimal tax model - Sita Nataraj Slavov; Weifeng Zhong (American Enterprise Institute (AEI), 2021)
Although the U.S. has a more progressive tax system than many other high-income countries, its overall fiscal system does less to reduce inequality because its tax system is smaller (OECD 2008). What societal preferences can explain these cross-country differences? We address this question by computationally solving a two-bracket optimal tax problem with lump sum redistribution. In this framework, a social planner can achieve redistributive goals by selecting progressive tax rates or scaling up the entire tax system to fund a larger transfer. We find that planners who exhibit stronger inequality aversion prefer tax systems that are similarly or slightly less progressive, but substantially larger, than the tax systems chosen by planners who exhibit weaker inequality aversion. These larger tax systems, like those in other high-income countries, result in greater reduction in inequality. In addition, planners who favor middle-income individuals or both low- and middle-income individuals (e.g., the bottom 99 percent of the distribution) prefer smaller, more progressive tax systems than planners who favor the lowest-income individuals. These smaller tax systems, like that of the U.S., result in less reduction in overall inequality.
Keywords: A; 330; Government; Income Redistribution; Inequality; Progressive Tax; Tax Code; Tax Rates; US Economy